Five-year Follow-up of Arthroscopic Superior Capsule Reconstruction for Irreparable Rotator Cuff Tears. Issue 3 (31st March 2019) - Mihata, Teruhisa; Lee, Thay Q.; Hasegawa, Akihiko; Fukunishi, Kunimoto; Kawakami, Takeshi; Fujisawa, Yukitaka; Itami, Yasuo; Ohue, Mutsumi; Neo, Masashi
Objectives: For irreparable rotator cuff tears, we developed a new surgical treatment—arthroscopic superior capsule reconstruction (SCR)—to restore superior shoulder stability, muscle balance, and shoulder function. The objective of this study was to assess (1) changes in functional outcome; (2) changes in graft thickness; (3) rates of graft tear; and (4) rates of glenohumeral osteoarthritis during a 5-year follow-up period. Methods: From 2007 to 2013, arthroscopic SCR using autograft of fascia lata was performed on 37 shoulders with irreparable rotator cuff tears. Seven patients were lost to follow-up. Consequently, 30 shoulders (mean age, 68.0 years) were enrolled in the study. Shoulder range of motion (ROM), American Shoulder and Elbow Surgeons (ASES) and Japanese Orthopaedic Association (JOA) scores, acromiohumeral distance (AHD), Hamada grade, and Goutallier grade were compared among before surgery, 1 year after SCR, and 5 years after SCR. Graft thickness, which was measured in MRI, was compared among 3 months, 1 year, and 5 years after SCR. One-way analysis of variance followed by Fisher's LSD post-hoc test was performed for statistical analysis. In addition, rates of return to sport or work were investigated in those patients who had been employed (12 patients: 5 carpenters, 5 farmers, and 2 construction workers) or played sports (8 patients: 2 table tennis, 1 golf, 1 martial arts, 1 yoga, 1 badminton, 1 mountain-climbing, and 1 ground golf) before injury. Results: Both ASES and JOA scores after arthroscopic SCR improved significantly at both 1 year ( P < 0.001) and 5 years after SCR ( P < 0.001). ASES score at 5 years after SCR was significantly better than that at 1 year after SCR ( P = 0.02). Postoperative ASES scores at both 1 year and 5 years after SCR were better in healed patients (27 patients) than in unhealed patients suffering from graft tear (3 patients). Active elevation was significantly improved at both 1 year and 5 years after SCR ( P < 0.001). At five years after SCR, 11 patients were still working and one patient, who had returned to part-time work at 1 year, had retired. All 8 patients were still playing sport before their injuries at 5 years after SCR. AHD was increased significantly at both 1 and 5 years after SCR ( P < 0.001). There was no significant difference in AHD between 1 and 5 years after SCR ( P = 0.16). In the 27 patients in whom the graft remained intact, graft thickness did not differ significantly among 3 months, 1 year, and 5 years after SCR ( P = 0.67). Hamada grade was significantly improved at both 1 and 5 years after SCR (preoperative: 2.3 ± 0.8; 1 year: 1.3 ± 0.7; 5 years: 1.3 ± 0.7, P < 0.001). All patients who had graft healing had no progression of glenohumeral osteoarthritis during the 5-year follow-up period. Two of the 3 patients with graft tear were suffering severe glenohumeral osteoarthritis (with narrowing of the glenohumeral joint space) at 5 years after SCR. The Goutallier grade did not change significantly after SCR in any patients. Conclusion: In a 5-year follow-up study, arthroscopic SCR restored shoulder function and resulted in high rates of return to recreational sport and work. Shoulder function and ROM were likely to get better with time. Graft tear exacerbated the clinical outcome after SCR and caused glenohumeral osteoarthritis in 2 of 3 patients by 5 years after SCR. Graft thickness and postoperative AHD did not change significantly between 1 and 5 years of follow-up, suggesting that we can expect excellent functional outcomes with long-term follow-up. Clinical outcome before and after arthroscopic SCR Before surgery 3 months after SCR 1 year after SCR 5 years after SCR ASES score (points) 29.0 ± 20.0 - 83.0 ± 16.0 92.3 ± 10.3 Active elevation (°) 85 ± 54 - 138 ± 38 151 ± 32 AHD (mm) 3.4 ± 2.2 - 9.1 ± 2.6 8.1 ± 3.2 Graft thickness (mm) - 7.5 ± 2.0 7.9 ± 2.1 7.8 ± 1.8